Interrelationship of economic growth and regional religious properties - Esa Mangeloja (European Regional Science Association (ERSA), 2004)
During the past few years, empirical economic growth modeling has emerged by constructing and testing numerous model and explanatory variable alternatives. One of the most promising recent idea consists that also religious aspects should be included as explanatory variables into economic growth models, therefore capturing influences of culture, moral and ethics. Moral institutions and ethics affect the economic development, as for example, trust and honesty are essential requirements for emerging economic activity. In this paper, analysis of economic growth extends from international to regional level. Religious activities and beliefs are documented over a long time period in many Western economies, making quantitative empirical time series data available. Firstly, following the idea and argumentation by Barro and Mc Cleary (2003a, 2002), “religious production efficiency” measure is constructed and used in economic growth regressions for8 OECD countries, proxying quantifiable dimensions of culture. By using panel estimation methods and additionally time-series estimations for each country, rather than usual cross-country regressions, more information is gained concerning the country specific growth and religion characteristics. Empirical evidence from the panel data estimations seems to suggest that religious beliefs attain more relevance than religious attendance. Religious production efficiency, containing both belief and activity aspects, was not found statistically significant with panel data or with individual 8 OECD countries growth model, except for Finland. Significant coefficient for Finland can be explained by referring to Finland's unique religious market properties, as the level of religious beliefs have historically been unusually high, and continue to be, in Finland. Secondly, interrelationship of Finland's religious and economic variables are analyzed in regional level. Three small Finnish cities, all with strong religious Christian revival background, gain positive and significant coefficients when consumer income growth is regressed by religious activity. Nevertheless, more exact understanding on the links between these concepts are essentially needed to better model the economic consequences of cultural, religious and moral variables. Therefore, several suggestions are presented to gain better growth information in the future empirical growth modeling, including better theoretical background, more robust estimation techniques and longer data.
Keywords: 330